2020
DOI: 10.1101/2020.07.25.20161745
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity and phylogeographic analysis of human herpesvirus type 8 (HHV-8) in two distant regions of Argentina: association with the genetic ancestry of the population

Abstract: Background: The genetic diversity of persistent infectious agents, such as HHV-8, correlates closely with the migration of modern humans out of East Africa which makes them useful to trace human migrations. However, there is scarce data about the evolutionary history of HHV-8 particularly in multiethnic Latin American populations. Objectives: The aim of this study was to characterize the genetic diversity and the phylogeography of HHV-8 in two distant geographic regions of Argentina and to establish potential… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…2015; Pérez and Tous 2017; Hulaniuk et al . 2020), the SBE technique described herein only needs 294 pb for genotype characterization. This difference is particularly important when genotyping must be carried out in low‐quality DNA samples, which are mostly derived from FFPE tissues (Pikor et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2015; Pérez and Tous 2017; Hulaniuk et al . 2020), the SBE technique described herein only needs 294 pb for genotype characterization. This difference is particularly important when genotyping must be carried out in low‐quality DNA samples, which are mostly derived from FFPE tissues (Pikor et al .…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, ORFK1 was amplified by a previously described nested PCR protocol (Hulaniuk et al . 2020) and bidirectionally sequenced by Big‐Dye Termination chemistry system (Applied Biosystem, Thermo Fisher Scientific). Multiple sequence alignments of ORFK1 sequences from the present study and reference strains reported in the GenBank were performed using BioEdit ver.…”
Section: Methodsmentioning
confidence: 99%